A formação inicial e continuada de trabalhadores das micro e pequenas indústrias de setores tradicionais de Curitiba : das gravatas que projetam e dos macacões que ensinam - Keller, Roberto Ranna (2015)
Resulting from reflections about socio-economic importance of small industries in Brazil, the thesis herein presented focus itself in researching professional training offered to initial levels for industrial areas at Curitiba, South Brazil. For such, it was researched which kind of contribution is offered by the government, professional schools, and small industries from Curitiba, in order to train these workers. Based on studies performed by Florestan Fernandes and Caio Prado Junior about the economic models, and Celso Furtado’s studies about the importance of the industrial chain for development, hypotheses are established regarding the professionalization processes for workers of these industries, branded by precariousness, according to Ricardo Antunes. In the same line, Frigotto, Ciavatta, Ramos, Moraes, Ferretti and Kuenzer, amongst others, also point to how much the precariousness of professional training has a negative effect on workers class’ lives in Brazil. Based on legislation numbers concerning professional training, proposed training courses and indicatives from the Código Brasileiro de Ocupações (CBO – Brazilian Occupational Codes) basic parameters have been established for what is, constitutionally, forecasted as required for basic professionalization on worker’s life. Field Research refers to such information, being performed together with six small industries from traditional productive segments at Curitiba, comprising food, graphic, furniture and clothing sector, highlighted either by plant numbers and intense job offering in this town. Having a qualitative character, besides visiting and observing the place and working environment at participants industries, it has been performed interviews with some workers – aiming to context their life path, their daily routines at the factory, their way to professionalization, difficulties in this process, their daily lives outside the working place, their frustrations and expectations as for their future – and employers – in order to present the circumstances under which those enterprises have arisen, their paths, opportunities and difficulties against the economic scenario, their routine, hiring processes, assessment, and the way they offer professional training as well. It has been concluded that professional training happens almost exclusively inside these small industries and that, due to lack of academic learning and to this precarious training, workers have their professional growth, life quality and future’s expectation committed, and on the other hand, companies lose their competitive viability due to difficulties to embody technologies demanding a wider and depth knowledge to their use. At last, provided they do not comply with workers and employers expectations, it was observed the lack of efficiency concerning the existing professional training courses which, from the knowledge they may offer, requires an analysis in order to promote better factory performances and better social conditions to workers.